Impact of Mycobacterium vaccae immunization on lung histopathology in a murine model of chronic asthma - AKKOÇ, TUNÇ (WILEY, 2003)
Background Therapeutic modalities of asthma have not been proved to be successful in reversing the already established chronic changes of airways. Objective We aimed to determine the impact of heat-killed Mycobacterium vaccae immunization, a potent Th1 stimulant, on chronic changes of asthma. Methods Newborn BALB/c mice were divided into three groups; mice in M. vaccae group received 10(7) colony-forming units (CFU)/50 muL of heat-killed M. vaccae subcutaneously on days 3, 14 and 42 before the development of chronic asthma model, whereas mice in control and chronic asthma groups received saline. Subsequently, mice in M. vaccae and chronic asthma groups were administered 10 mug/100 muL of ovalbumin (OVA) on days 43, 45, 47, 49, 51, 53 and 55 intraperitoneally, and 20 mug/10 muL of OVA on days 83, 86 and 89 intratracheally. Mice in control group received saline on the same days. Results Comparison of M. vaccae and chronic asthma groups showed statistically significant differences in goblet cell numbers, thickness of basement membrane and subepithelial smooth muscle of small, medium and large airways and epithelial thickness of medium airways. There was no significant difference between the control and M. vaccae groups except for goblet cell numbers of medium and large airways, and epithelial thickness of medium airways. Conclusion Results of our study suggested that immunization by M. vaccae of newborn mice would prevent some of the chronic changes of airways due to asthma.
Keywords: airway remodelling; asthma; BALB/c; Mycobacterium vaccae; SENSITIZED NEWBORN MICE; T-CELL CYTOKINES; MODULATION; OVALBUMIN; BOVIS; TUBERCULOSIS; RESPONSES; ALLERGEN; PATTERNS